Upending the status quo through transformative adaptation: A systematic literature review. (April 2020) - Ajulo, Oluwadunsin; Von-Meding, Jason; Tang, Patrick
Abstract: Disaster studies is replete with common expressions and concepts. A particularly revolutionary concept has increasingly appeared in the discourse in recent years - transformative adaptation (most often expressed as "transformation"). These terms have been used to represent fundamental change from a status quo based on processes that create vulnerability. Coined as a form of adaptation, transformative adaptation seeks bottom-up and long-term changes that reduces vulnerability. However, despite increasing interest in the concept, the overall understanding of its practicability and potential outcomes remains fragmented. In this paper we present the results of a systematic literature review undertaken to assess the current state of knowledge regarding transformative adaptation in existing literature and identify opportunities for further research. The research uses a well-defined protocol for identifying relevant academic papers on transformative adaptation and the findings are analyzed using both qualitative and quantitative tools. Findings from the systematic review highlight the complex nature of change, key theories used in the study of transformative adaptation, the variables necessary for its application and the interdependencies among the variables. This provides a theoretical foundation for future practical application of the concept by highlighting variables and measures to implement and assess transformative adaptation in real life situations.